Faktor Penyebab dan Upaya Penanggulangan Terhadap Tindak Pidana Penyelundupan Impor Pakaian Bekas di NTT - Ismawati Jamaludin; Thelma S.M Kadja; Rosalind Angel Fanggi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
The act of smuggling is a crime of illegally or illegally importing or removing goods to avoid duties that can harm the state. This study aims to identify the causal factors and countermeasures against the crime of smuggling the import of used clothes in East Nusa Tenggara (NTT). The method used is empirical juridical with data collection techniques in the form of data obtained directly from the community through interview techniques and document studies then analyzed and compiled systematically. The results of the study show that the factors that cause these crimes include geographical factors, industrial conditions in NTT, transportation, mentality and society. Countermeasures consist of two categories: first, non-penal (preventive) efforts which include observation and patrol activities; Second, penal (repressive) efforts which include supervision, enforcement, and review of regulations. Smuggling crimes that occur in East Nusa Tenggara generally often occur due to the lack of a security system in the area where the entry and exit of goods in the port and the presence of individuals who back up these activities, so the accuracy and tenacity of investigators in solving this smuggling case is very necessary.